The Aftermath of War in “The End and the Beginning” by Wislawa Szymborska - Piele, Maria Diana (International Journal of Language and Literary Studies, 2024)
This study is an analysis of the poem “The End and the Beginning” by Wis?awa Szymborska. It offers a cyclical perspective framed in an ethical dilemma that encourages readers to long reflection. Few other works have thoroughly examined the English version of this poem, so the present paper provides an analysis of meaning by looking at themes like collective guilt, forgetting, and renewal. Among the ruins, Szymborska explores how society chooses to “cleanse” its memories, preferring to forget rather than understand history. She highlights the conflict between remembering and forgetting, bemoaning humanity’s failure to break free from the cycle of conflict while paying tribute to those who persevere and keep trying. She captures the repetitive nature of destruction and reconstruction that defines human history. The conclusion suggests that genuine healing cannot take place unless the past is faced head-on and its history is responsibly assumed.